O efeito moderador da virtualidade na relação entre a comunicação e o sucesso em projetos - Medeiros, Onilio Firmino de (2020)
Due to the growing improvement of the companies' computerized environment and the search for the improvement of efficiency in projects, there is a growing demand for local teams to work with virtual teams. Research reveals that listening and verbal communication have been ranked by experts in the top 10 on a list of 50 key competencies for project managers to succeed in organizational environments. Virtuality imposes greater complexity on project teams for management and adds factors that measure virtuality when comparing virtual teams with local teams. In this context, the objective of this research is to determine at what level virtuality moderates the relationship between communication and the success of projects. The research is delineated in three phases: in the first phase, the theme was delimited and an exploratory research in which they were used the base of Web of Science and Scopus databases. In the second phase, with a qualitative approach, aiming at understanding the research objectives, we opted for a Systematic Literature Review (SLR), which allowed us to proceed with the analysis of the research corpus. In the third phase, with a quantitative approach and using validated scales of communication themes, virtuality and project success, it was started the field research with professionals in the project management area, in order to answer the following research question: How is the relationship between communication and project success moderated by the level of virtuality? A survey of 347 respondents from several countries around the world was applied to conduct the survey. The research results indicate that the variables of communication, satisfaction and effectiveness of communication positively influence the success of projects in the context of local or virtual teams. In addition, the research suggests that virtuality negatively moderates the relationship between communication satisfaction and success in projects, in the virtual context, in addition to the relationship of communication effectiveness and success in projects, in the local context. From the results, it is understood that direct and indirect actions to enhance the team´s communication, contribute to the success of projects and add competitive advantages to companies.